The first complete chloroplast genome of Fagopyrum leptopodum (Diels) Hedberg (Caryophyllales: Polygonaceae) with phylogenetic implications. Issue 8 (3rd August 2021) - Ye, Xueling; Wang, Luo; Xiang, Dabing; Sun, Yanxia
Abstract: In the present study, we sequenced and assembled the complete chloroplast genome of Fagopyrum leptopodum (Diels) Hedberg. The chloroplast genome of F. leptopodum was composed of 85 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. The F. leptopodum chloroplast genome is 159, 375 bp in length, with a GC content of 37.81%. Phylogenetic analysis based on the combined chloroplast gene dataset indicated that the F. leptopodum exhibited a close relationship with Fagopyrum luojishanense .